Hematological and Serum Chemistry Values for the Ring-necked Pheasant (Phasianus colchicus): Variation with Sex and Age - Schmidt, Elizabeth Moreira dos Santos; Paulillo, Antonio Carlos; Santin, Elizabeth; Dittrich, Rosangela Locatelli; Oliveira, Edson Goncalves de (International Journal of Poultry Science, 2007)
The influences of sex and age on hematological parameters were investigated in the ring-necked pheasant. Statistical comparisons were made for differences in values between male and female, 30 adults (52 week old) and 20 juvenile birds (5 week old). A variety of blood parameters showed statistically significant age and sex related differences. Adult males had higher values for Packed Cell Volume (PCV) and juveniles lower values for PCV. Adult females had higher values for basophils, the heterophil/lymphocyte ratio and total plasma protein. Juvenile females had higher values for hemoglobin. Adults had greater White Blood Cells (WBC), heterophils, eosinophils and monocytes. Serum biochemical values (uric acid, gamma glutamyl transferase, protein, albumin and globulins) were determined in young (5 week old) ring necked pheasants. There were no differences in any of these serum parameters among juvenile males and females.